Attitudes and drivers' behavior on safe mobility in Malaysia - Ali, Noor Malinjasari; Mohamed Nor, Raslina; Borhanuddin, Rahayu Izwani; Kamaruddin, Kardina; Mokhlas, Hasmi; Mohd Noor, Hasmida (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
Safe mobility is a crucial factor for both rural and urban communities and it is indeed a human need to feel safe. The global transport agenda is also focusing on safe mobility need as part of achieving sustainable environment. However, road transport accidents are still a major threat to achieve sustainability, as the cause of deaths because of road accidents is placed at number nine for worldwide death (Mohamed and Bromfield, 2017).